Taxonomic review of the millipede genus Touranella Attems, 1937, with a redescription of the type species, T. gracilis Attems, 1937, and descriptions of three new species from Laos (Diplopoda, Polydesmida, Paradoxosomatidae) - Natdanai Likhitrakarn; Sergei I. Golovatch; Khamla Inkhavilay; Somsak Panha; Chirasak Sutcharit (ZooKeys)
The flat-back millipede genus Touranella Attems, 1937 is currently comprised of 13 species, including three new ones from Laos: T. chenla Likhitrakarn, sp. nov., T. srisonchaii Likhitrakarn, sp. nov., and T. jaegeri Likhitrakarn, sp. nov. The generic diagnosis is updated, a key is given to all known species, and their distributions are mapped. Additionally, T. gracilis, the type species of Touranella from Vietnam, has been redescribed and illustrated based on type specimens.